Infrared Glass–Ceramics with Multidispersion and Gradient Refractive Index Attributes. (24th June 2019) - Sisken, Laura; Kang, Myungkoo; Veras, Johann M.; Lonergan, Charmayne; Buff, Andrew; Yadav, Anupama; McClane, Devon; Blanco, Cesar; Rivero‐Baleine, Clara; Mayer, Theresa S.; Richardson, Kathleen A.
Abstract: Infrared (IR) glass–ceramics (GCs) hold the potential to dramatically expand the range of optical material solutions available for use in bulk and planar optical systems in the IR. Current material solutions are limited to single‐ or polycrystalline materials and traditional IR‐transparent optical glasses. GCs that can be processed with spatial control and extent of induced crystallization present the opportunity to realize an effective refractive index variation, enabling arbitrary gradient refractive index elements with tailored optical function. This work discusses the role of the parent glass composition and morphology on nanocrystal phase formation in a multicomponent chalcogenide glass. Through a two‐step heat treatment protocol, a Ge–As–Pb–Se glass is converted to an optical nanocomposite where the type, volume fraction, and refractive index of the precipitated crystalline phase(s) define the resulting nanocomposite's optical properties. This modification results in a giant variation in infrared Abbe number, the magnitude of which can be tuned with control of crystal phase formation. The impact of these attributes on the GCs' refractive index, transmission, dispersion, and thermo‐optic coefficient is discussed. A systematic protocol for engineering homogeneous or gradient changes in optical function is presented and validated through experimental demonstration employing this understanding. Abstract : Multicomponent chalcogenide glasses with the composition of (GeSe2 –3As2 Se3 )1− x PbSe x where x = 0–40 mol% are fabricated, and their microstructure, refractive index, transmission, dispersion, and thermo‐optic coefficient is characterized. These glasses are then heat‐treated to determine how crystal phase formation affects the optical properties. Dispersion characteristics of the base glass and post‐processed glass–ceramics are compared to other infrared materials.